Podophyllotoxin and Rutin Modulates Ionizing Radiation-Induced Oxidative Stress and Apoptotic Cell Death in Mice Bone Marrow and Spleen - Singh, Abhinav; Yashavarddhan, M. H.; Kalita, Bhargab; Ranjan, Rajiv; Bajaj, Sania; Prakash, Hridayesh; Gupta, Manju Lata (Frontiers in Immunology, 2017)
Present study is aimed to investigate the radioprotective efficacy of G-003M (combination of podophyllotoxin and rutin) against gamma radiation-induced oxidative stress and subsequent cell death in mice bone marrow and spleen. Prophylactic administration of G-003M (-1h) rendered more than 85% survival in mice exposed to 9 Gray (lethal dose) with dose reduction factor (DRF) of 1.26. G-003M pre-treated mice demonstrated significantly reduced level of reactive oxygen species, membrane lipid peroxidation and retained glutathione level. In the same group, we obtained increased expression of master redox regulator, Nrf-2 and its down-stream targets (Ho-1, Nqo-1, Gst and Txnrd-1). In addition, G-003M pre-administration has also shown a significant reduction in Keap-1 level (Nrf-2 inhibitor). Radiation-induced lethality was significantly amended in combination treated (G-003M) mice as demonstrated by reduced 8-OHdG, annexin-V FITC positive cells and restored mitochondrial membrane potentail. Expression of anti-apoptotic protein Bcl-2 and Bcl-xL was restored in G-003M pre-treated group. However, pro-apoptotic proteins (Puma, Bax, Bak, Caspase-3 and Caspase-7) were significantly declined in this group. Further analysis of immune cells revealed G-003M mediated restoration of CD3 and CD19 receptor which was found decreased to significant level following irradiation. Similarly Gr-1, a marker of granulocytes, was also retained by G-003M administration prior to radiation. Modulatory potential of this formulation (G-003M) can be exploited as a safe and effective countermeasure against radiation induced lympho-hemopoietic injury.